LUBUK LARANGAN: AN ANALYSIS OF CULTURAL AND SPACIAL APPROACHES INCORPORATING CULTURAL AWARENESS IN FLOOD DISASTER MITIGATION EFFORTS IN BAHOROK - Nainggolan, William Jordan; Siwi, Riri Putri; Faturrahman, Rifki; Zhafirah, Alya; Br. Tarigan, Putri Yola Endayanti; Febryani, Ayu (Universitas Negeri Medan, 2025)
Bahorok Subdistrict is one of the subdistricts in Langkat Regency, North Sumatra, known for the Bahorok River, which has experienced flooding in 2003, 2015, and most recently in 2023. Given this, natural disasters such as flooding pose a crucial risk to the sustainability of tourism in Bahorok Subdistrict if mitigation efforts are not planned effectively. Therefore, this study aims to analyze the implementation of*lubuk larangan* as a flood disaster mitigation effort in Bahorok Subdistrict, examine the cultural approach with cultural awareness appliedto *lubuk larangan* as a flood disaster mitigation strategy, and analyze spatial factors that need to be considered in developing flood disaster mitigation strategies in Bahorok Subdistrict. This research explores the role of *lubuk larangan* as a cultural and spatial approach in flooddisaster mitigation in Bahorok Subdistrict, Langkat Regency, North Sumatra. It employs a mixed-methods approach with an embeddeddesign, combining qualitative and quantitative strategies. Data were collected through participant observation and questionnaires distributed to 60 respondents around the Bahorok River. Qualitative analysis was conducted through ethnographic interviews, domain analysis, and taxonomy, while quantitative analysis used descriptive statistical tests and Geographic Information System (GIS) to produce spatial maps related to flood potential. The study found that the implementation of *lubuk larangan*, initiated by local communities, is effective in preserving river ecosystems and serves as a form of non-structural disaster mitigation. The community's cultural awareness of *lubuklarangan* is still at the level of cultural consideration. Spatial factors such as topography, land slope, and land use are also crucial indeveloping flood mitigation strategies. The findings are expected to contribute significantly to river conservation efforts and community safety around the Bahorok River. Key words: Cultural, Spatial, Mitigation, Flood, Bahorok